2009
DOI: 10.1002/app.29493
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and mechanical properties of copolymers of methyl methacrylate with N‐aryl itaconimides

Abstract: ABSTRACT:The article describes the preparation of cast copolymer sheets of methyl methacrylate with varying mole fractions of N-(p-methoxyphenyl) itaconimide/ N-(2-methoxy-5-chlorophenyl) itaconimide/N-(3-methoxy-5-chlorophenyl) itaconimide monomers by bulk copolymerization using azobisisobutyronitrile as an initiator. The effect of incorporation of varying mole fractions of N-arylsubstituted itaconimides in poly(methyl methacrylate) (PMMA) backbone on the thermal, optical and physicomechanical properties of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…1 H, 13 C and 19 F NMR spectra of intermediates were recorded on a JEOL resonance ECZ 400S spectrometer (400 MHz) in CDCl 3 . Tetramethylsilane (TMS) and CDCl 3 were used as internal standards for 1 H and 13 C NMR, respectively; CF 3 CO 2 H was used as an external standard for 19 F NMR.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 H, 13 C and 19 F NMR spectra of intermediates were recorded on a JEOL resonance ECZ 400S spectrometer (400 MHz) in CDCl 3 . Tetramethylsilane (TMS) and CDCl 3 were used as internal standards for 1 H and 13 C NMR, respectively; CF 3 CO 2 H was used as an external standard for 19 F NMR.…”
Section: Measurementsmentioning
confidence: 99%
“…[1][2][3][4] However, the glass transition temperature (T g , 100 C) and heat-deformation temperature of PMMA are relatively low so as to limit its applications. 5,6 In order to improve T g and the thermal stability of PMMA, investigators have explored various methods, 3, [7][8][9][10][11][12][13][14][15] including the copolymerization of methyl methacrylate (MMA) with comonomers bearing rigid or bulky groups to overcome the miscibility puzzle, or the formation of a threedimensional network structure by the addition of crosslinking agent. Wilkie et al prepared MMA-DVB crosslinked polymers using divinylbenzene (DVB) as crosslinking agents and the degradation temperature (T d,5% ) of resulting polymers increased from 162 C to 294 C. 12 Kuo et al suggested an approach to raise the T g of PMMA through copolymerization with methacrylamide (MAAM) since hydrogen-bonding interactions exist between these two monomer segments.…”
Section: Introductionmentioning
confidence: 99%
“…To raise T g of PMMA, copolymers incorporating monomers with rigid or bulky structures have been reported widely . For example, copolymerization of methyl methacrylate (MMA) with maleimide (MI) which has a five‐member ring was discussed by Kita et al .…”
Section: Introductionmentioning
confidence: 99%
“…To raise the value of T g , PMMA copolymers incorporating rigid or bulky monomer structures 2,3 or monomers that can form hydrogen bonds with the carbonyl groups of PMMA have been reported widely. [4][5][6][7][8][9] Previously, the copolymerization with methacrylamide (MAAM) through hydrogen bonding interactions can raise the value of T g of PMMA [10][11][12][13] due to compositional heterogeneities in hydrogen bonded copolymers. 14,15 However, in these previous studies, [4][5][6][7][8][9][10][11][12][13] the monomers only possessed relatively weak single hydrogen bonding moieties and such intermolecular interactions must be present at relatively high mole percentages to enhance the thermal behavior of copolymers; therefore, the structures of the copolymers differ substantially from those of their unmodified polymers.…”
Section: Introductionmentioning
confidence: 99%
“…100°C) limited the use in optical electronics industry, for materials such as compact discs (CD), optical glasses, and optical fibers, because it undergoes distortion when used in an inner glazing material. To raise the value of T g , PMMA copolymers incorporating rigid or bulky monomer structures2, 3 or monomers that can form hydrogen bonds with the carbonyl groups of PMMA have been reported widely 4–9. Previously, the copolymerization with methacrylamide (MAAM) through hydrogen bonding interactions can raise the value of T g of PMMA10–13 due to compositional heterogeneities in hydrogen bonded copolymers 14, 15.…”
Section: Introductionmentioning
confidence: 99%